Age-Related Variability in Cortical Activity During Language Processing. - Fridriksson, Julius; Morrow, K. Leigh; Moser, Dana (Journal of Speech, Language & Hearing Research, 2006)
Purpose: The present study investigated the extent of cortical activity during overt picture naming using functional magnetic resonance imaging (fMRI). Method: Participants comprised 20 healthy, adult participants with ages ranging from 20 to 82 years. While undergoing fMRI, participants completed a picture-naming task consisting of 60 high-frequency nouns. Results: Linear regression analysis revealed a positive relationship between age and cortical activation intensity in Broca's and Wernicke's areas as well as the right-hemisphere homologue of Broca's area. In contrast, neural activity in the anterior cingulate gyrus, an area thought to be involved in attentional processing, did not increase as a function of age. Conclusions: These findings suggest age-related increases in cortical activation during simple language tasks, such as picture naming, in brain areas typically associated with language processing. Reprinted by permission of the publisher.